Comparative evaluation of quality of different brands of Amoxicillin capsules available in community pharmacies in Jaffna, Sri Lanka - Abeysinghe, M.D.; Zahra, M.F.F.; Thuvaragan, S.; Surenthirakumaran, R.; Senadeera, H.K.P.A. (Proceedings of the 11th YSF Symposium - 2023, 2023)
Amoxicillin is a semisynthetic, β lactam antibiotic that is extensively prescribed among antibiotics. The effectiveness of drug therapy can be changed according to the amount of active ingredients in the dosage forms. Lack of quality may lead to toxicity or failure of therapeutic goals and may develop resistance. Therefore, this study aims to evaluate and compare the quality of different brands of Amoxicillin capsules with innovator brand purchased from private pharmacies in the Jaffna municipal area. Commonly available 7 brands of Amoxicillin 250mg capsules were collected from community pharmacies of the Jaffna municipal area and coded from A1 to A7. Qualities of those brands were determined by using the methods such as weight variation, dissolution, and uniformity of content tests as described in British Pharmacopoeia (BP). The dissolution profile data of seven brands were compared with the innovator brand (Amoxil) using Oneway ANOVA followed by the Dunnett T3 test. All the tested brands complied with the official specifications for weight variation and dissolution tests. All brands of Amoxicillin Trihydrate capsules complied with the specified BP limits except brand A4 which failed to release the stated amount (89.9 % ±0.15). The statistical comparison for the drug release reported that some of the brands showed significant differences (p < 0.05), indicating that the in vitro drug release would affect their in vivo bioavailability. Authorities of the country should take more attention to the quality of antibiotics, especially imported drugs.
Keywords: Amoxicillin capsules; Quality; Evaluation; Sri Lanka